The Role of Formononetin in Cerebral Ischemia-Reperfusion Injury: A New Mediator of c-Fos/IL-10/STAT3 Signaling Pathway - Ming Yan; Fuyong Ni; Xue Xie; Chenfeng Zhang; Jing Zhu (Frontiers in Bioscience-Landmark)
Backgrounds: Inflammation plays a pivotal role in the advancement of ischemic stroke, and Formononetin has been recognized for its potential benefits due to its anti-inflammatory effects. Although Formononetin shows promise for reducing cerebral ischemic injury, its precise effectiveness and the underlying molecular mechanisms still need to be thoroughly explored. The research aimed to investigate Formononetin’s impact and mechanisms on ischemic brain damage. Methods: In this study, both the ischemia/reperfusion (I/R) mouse model and the oxygen-glucose deprivation/reperfusion (OGD/R) cell model were used. The I/R mouse model was prepared using the middle cerebral artery occlusion (MCAO) method, while the OGD/R SH-SY5Y cell model was established using the oxygen-glucose OGD/R method. Hematoxylin and Eosin (H&E) staining, Tunnel fluorescence staining, and Nissl staining were employed to observe the effects of Formononetin on neuronal damage, apoptosis, and survival in I/R mouse brain tissue. Additionally, the effects of Formononetin on the levels of pro-inflammatory factors in I/R mice and OGD/R cells were detected using Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR) and Enzyme-Linked Immunosorbent Assay (ELISA) methods. The c-Fos/Interleukin-10 (IL-10)/Signal Transducer and Activator of Transcription 3 (STAT3) signaling pathway in I/R mice and OGD/R cells was examined using RT-qPCR and Western Blot (WB). Furthermore, rescue validation was performed using targeted interventions of IL-10 and c-Fos, confirming that the c-Fos/IL-10/STAT3 signaling pathway is a key target of Formononetin. Results: Our findings reveal that Formononetin notably decreased infarct size and neuronal damage in vivo (p < 0.001). Additionally, Formononetin decreased inflammation and lowered levels of pro-inflammatory cytokines (p < 0.05). In cell models, Formononetin effectively suppressed neuronal injury induced by OGD/R and the related inflammatory markers (p < 0.001). Mechanistic studies showed that Formononetin enhances IL-10 expression in both models of ischemic brain injury, a process crucial for its protective effects against inflammation (p < 0.05). This regulation is facilitated by increased nuclear translocation of c-Fos, highlighting the c-Fos/IL-10/STAT3 pathway as a crucial mechanism of Formononetin’s neuroprotective and anti-inflammatory effects in cerebral ischemia (p < 0.05). Conclusion: We found Formononetin alleviates inflammation associated with I/R injury by activating the c-Fos/IL-10/STAT3 pathway, which highlights the potential of Formononetin as a promising therapeutic approach for I/R injury.